1989
DOI: 10.3109/00207458908987432
|View full text |Cite
|
Sign up to set email alerts
|

Hemisphere Asymmetry of Alpha Burst Frequency of Occurrence Variations in Depression

Abstract: A new EEG index (Alpha Burst Occurrence Variability Index: alpha BVI) has been designed for quantifying the sequential variability of the frequency of occurrence of alpha bursts, expressed on a cumulative graph (periodogram). EEG (P3-Fz and P4-Fz) was recorded during a rest situation: 1) in two groups of right handed depressed patients, characterized, one by psychomotor retardation (PMR group), the other by blunted affect (BA group); 2) in a group of right handed controls. In both groups of patients, before tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…All participants were native Koreans. Inclusion criteria for the participants were as follows: (1) [33,34] rating scales were evaluated in patients with MDD. Positive and Negative Syndrome Scales [35] were evaluated in patients with schizophrenia.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…All participants were native Koreans. Inclusion criteria for the participants were as follows: (1) [33,34] rating scales were evaluated in patients with MDD. Positive and Negative Syndrome Scales [35] were evaluated in patients with schizophrenia.…”
Section: Participantsmentioning
confidence: 99%
“…Although electroencephalographic frontal alpha asymmetry (FAA) has been suggested to be a clinical biomarker for the abnormalities in major depressive disorder (MDD) [1][2][3][4][5][6][7][8][9], conflicting results in prior research have contested this view [10,11]. A previous meta-analysis of 1883 individuals with MDD and 2161 healthy controls found that FAA's diagnostic value was not significant [11].…”
Section: Introductionmentioning
confidence: 99%
“…Although electroencephalographic frontal alpha asymmetry (FAA) has been suggested to be a clinical biomarker for the abnormal behavioral phenotype of major depressive disorder (MDD) [1][2][3][4][5][6][7][8][9], con icting results in prior research have contested this view [10,11]. A previous meta-analysis of 1,883 individuals with MDD and 2,161 controls found that FAA's diagnostic value was not signi cant [11].…”
Section: Introductionmentioning
confidence: 99%
“…Although electroencephalographic frontal alpha asymmetry (FAA) has been suggested to be a clinical biomarker for the abnormalities in major depressive disorder (MDD) [1][2][3][4][5][6][7][8][9], conflicting results in prior research have contested this view [10,11]. A previous meta-analysis of 1,883 individuals with MDD and 2,161 healthy controls found that FAA's diagnostic value was not significant [11].…”
Section: Introductionmentioning
confidence: 99%